Biochemical comparison of four commercially available C1 esterase inhibitor concentrates for treatment of hereditary angioedema - Feussner, Annette (Transfusion, 2014)
BACKGROUND: For safe and efficacious treatment of hereditary angioedema, C1 esterase inhibitor (C1-INH) concentrates should have high purity and high amounts of functional protein. As no pharmacopoeia requirements exist for C1-INH concentrate lot release, biochemical characteristics as declared by the manufacturers may not be compared directly. This study compared the characteristics and purity profiles of four commercially available C1-INH concentrates. STUDY DESIGN AND METHODS: The analysis included one transgenic (Ruconest) and three plasma-derived (Berinert, Cetor, Cinryze) C1-INH concentrates. C1-INH antigen concentration was determined by nephelometry, total protein (specific activity) with a Bradford assay, purity by size-exclusion chromatography and gel electrophoresis, and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry was performed. RESULTS: Functionality (inversely proportional to antigen-to-activity ratio) was lowest for Ruconest (1.67), followed by Cetor (1.42), Berinert (1.24), and Cinryze (1.22). Specific activity (U/mg) and purity (%) were highest in Ruconest (12.13; 98.6) and Berinert (11.57; 97.0), followed by Cinryze (10.41; 89.5) and Cetor (9.01; 88.6). Main protein bands were found for all plasma-derived products at approximately 105 kDa, and for Ruconest, at approximately 98 kDa. Additional bands in the plasma-derived products were α1-antichymotrypsin, ceruloplasmin, Factor C3 (Cinryze/Cetor), and immunoglobulin heavy constant mu (Berinert). CONCLUSION: Ruconest has a very high purity profile but is not identical to the human C1-INH protein. Of the plasma-derived products, Berinert has the highest purity profile. The impact of the nontherapeutic proteins identified has not yet been evaluated. For harmonization of the analysis for drug release, we recommend the establishment of regulatory requirements for purity determination and the implementation of threshold levels in C1-INH concentrates.